Academic Performance of Children with Autism in the Inclusion Program: A Case Analysis - Silin, Merriam S. (International Journal of Psychosocial Rehabilitation, 2026)
Children with Autism (CWAs) is catered in Inclusion Program of the Department of Education in the Philippines. It commits to provide them with the best education possible in the regular classroom. As it has been existing for many years and with the number growing every year in the public schools, it has become significant to critically determine the effects of the program to the academic performance of CWAs. A qualitative case study research design was utilized involving method triangulation of observation, in-depth individual interviews and documentary analysis. It revealed that the CWAs can now tell the big ideas/concepts implied in the story read, take note on the significant details of the story and poem read, understand the meaning and purpose of something, and decide based on their reasoning unlike when they were in SPED school. Furthermore, the CWAs are able to investigate and observe things around them and answer the questions of the teacher during recitations and discussions which were not observed from them on their previous SPED schools. With this, regular classroom teachers, school administration including the parents and other stakeholders may plan, develop and implement effective classroom activities and exercises for children with autism to address their needs in the regular class, so that they may be able to improve their test results, grades in the report card and their overall academic performance.